Reforming teacher salary policy to strengthen human capital development in Indonesia 2045 - Kartiko, Nafis Dwi; Gultom, Alex Oktobertus Pandapotan (Privietlab, 2026)
This study aims to explore teacher salary schemes as a strategic instrument for strengthening human capital formation in the context of Indonesia Emas 2045. This study uses a qualitative approach to understand the relationship between teacher compensation and human capital quality through a conceptual and contextual analysis. The literature review method was chosen because it systematically examines theories, empirical findings, and regulatory frameworks. The main sources of research include laws and regulations governing teacher welfare, official reports from state institutions such as the Central Statistics Agency and the Ministry of Education, and international publications, including the OECD, which provide cross-country comparative data. The data collection strategy involved selecting documents with high credibility, direct relevance, and up-to-date information, which were then analyzed using content analysis techniques that emphasized categorization, interpretation, and synthesis. The results of the study show that teacher salary policy reform is a strategic prerequisite for strengthening the quality of human capital and accelerating Indonesia's competitiveness. Evidence from the 2022 PISA results, which show a decline in mathematics, reading, and science achievement, confirms the urgency of improving instructional quality based on teacher welfare and professionalism in Indonesia. Human capital theory explains that investing in educators as knowledge producers can increase productivity and drive long-term growth through skill accumulation and innovation diffusion. Literature findings show that adequate compensation strengthens motivation, retention, and pedagogical commitment, whereas low salaries correlate with a decline in teaching performance and student engagement.